Characteristics of domestic predictors of persistent bronchial asthma in adolescents and allergic rhinitis in children with a distal occlusion - Shumna, T. Ye.; Nedelska, S. M.; Fedosieieva, O. S.; Zinchenko, T. P.; Шумна, Таміла Євгенівна; Недельська, Світлана Миколаївна; Федосєєва, Ольга Віталіївна; Зінченко, Тетяна Петрівна; Шумная, Т. Е.; Недельская, С. Н.; Федосеева, Е. С.; Зинченко, Т. П. (Запорожский государственный медицинский университет, 2018)
Purpose. Determination of domestic predictors of bronchial asthma in adolescents and allergic rhinitis in children with distal occlusion who have a persistent clinical course of the disease. Materials and methods. A clinical, anamnestic and allergic examination of 87 adolescents aged 13 to 17 years has been conducted. Of them, 34 adolescents with persistent bronchial asthma were considered as the first monitoring group (І); the group II included 28 children with persistent allergic rhinitis and distal occlusion, thereby they additionally received orthodontic treatment for faciomaxillary pathology. The control group (ІІІ) consisted of 25 healthy children. The ratio of boys to girls in the observation and control groups was the same (P > 0.05). Questionnaire method was used for the anamnestic data on living, social and hygienic conditions study: current household pet-keeping practice, frequency and specifications of certain cleaning agents and cosmetic products use in children. Also the clinical course of diseases and the subsequent dispensary observation in the remission period of children with persistent bronchial asthma and allergic rhinitis have been analyzed; an allergic study has been conducted in the absence of contraindications for in vivo testing with allergens by the use of skin prick tests with household and epidermal allergens produced by the Limited Liability Company “Immunologist” (Vinnytsia). When comparing statistical aggregates the non-parametric statistical method 2 × 2 Table, the Chi-square test (df = 1) were used and the odds ratio (OR) was calculated using the four-fold table with diagnostic interval (DI) calculation using the Woolf method. By the nonparametric gamma correlation method, recommended for use when there are many matching values in the data, the relationship between hypersensitivity indicators to allergens has been analyzed. A P-value of less than 0.05 was considered statistically significant. Results. Persistent course of chronic moderate allergic respiratory syndrome trended significantly higher in children with allergic rhinitis and distal occlusion (75.00%) than in adolescents with bronchial asthma (32.35 %). Household predictors of allergic diseases development in surveyed children were living in homes which were not renovated for over 10 years and keeping animals (for adolescents with asthma OR = 3.56, DI [1.08, 11.68] and OR = 6.27, DІ [1.26; 31.29]; for children with allergic rhinitis and distal occlusion OR = 4.62, DI[1.35; 15.78] and OR =6.39, DІ [1.24; 32.89]. Hypersensitivity to domestic dust allergens (35.29 %), Dermatophagoides pteronyssinus (29.41 %) house dust mites, epidermis of cats (23.53 %) has been diagnosed in adolescents with bronchial asthma and to house dusts Dermatophagoides pteronyssinus (50.00 %) and Dermatophagoides farinae (42.86 %), house dust mites (42.86 %), cat (42.86 %) and rabbit (17.86 %) epidermis has been revealed in children with allergic rhinitis and distal occlusion. Cosmetics, shampoos, bathing soaps containing formaldehyde, parabens, triclosan, sodium lauryl sulfate and surface-active agents for dishwashing were significantly more often used in the families of children with allergic diseases than in healthy families. Conclusions. Prevention of bronchial asthma in adolescents and allergic rhinitis and distal occlusion in children included the elimination treatment, prescription of allergen-specific immunotherapy according to positive results of allergy testing, living conditions improvement with timely repairs in their homes, use of hypoallergenic cosmetics, shampoos, soaps, gels, detergents for dishwashing without surface-active agents or careful rinsing under running water. Мета роботи – визначення побутових предикторів розвитку бронхіальної астми в дітей-підлітків та алергічного риніту в дітей із дистальним прикусом, що мали персистуючий клінічний перебіг захворювання. Матеріали та методи. Здійснили клініко-анамнестичне та алергологічне дослідження 87 дітей підліткового віку (від 13 до 17 років). У І групу спостереження ввійшли 34 підлітки із персистуючим перебігом бронхіальної астми, ІІ групу – 28 дітей із персистуючим алергічним ринітом і дистальним прикусом, які додатково лікували супутню зубощелепо-лицьову патологію в лікаря-ортодонта. Контрольна група спостереження (ІІІ) – 25 здорових дітей. Співвідношення хлопчиків і дівчаток у групах спостереження та контролю було однаковим (р > 0,05). За анкетуванням вивчили анамнестичні дані щодо побутових умов проживання, соціально-гігієнічний стан житла: наявність домашніх тварин, частоту та особливості використання певних хімічних мийних і косметичних засобів у дітей. Проаналізували клінічний перебіг захворювань. Під час диспансерного спостереження в періоді ремісії дітям із персистуючим перебігом бронхіальної астми та алергічного риніту за відсутності протипоказань до тестування in vivo з алергенами виконали алергологічне дослідження шляхом постановки шкірних прик-тестів із побутовими й епідермальними алергенами виробництва ТОВ «Імунолог» (м. Вінниця). Порівнюючи статистичні сукупності, використовували непараметричний статистичний метод «2×2 Table», the Chi-square (df = 1) та розраховували відношення шансів (ВШ) з використанням чотирьохпільної таблиці з розрахунком довірчого інтервалу (ДІ) за методом Woolf. З використанням непараметричного методу gamma correlation (рекомендується використовувати, коли в даних є багато значень, котрі збігаються) виконали аналіз зв’язку між показниками гіперчутливості до алергенів. Розбіжності р < 0,05 при порівнянні показників у групах спостереження та контрольній вважали статистично вірогідними. Результати. Персистуючий перебіг хронічного алергічного респіраторного синдрому середнього ступеня тяжкості вірогідно частіше реєстрували в дітей з алергічним ринітом і дистальним прикусом (75,00 %), ніж у підлітків із бронхіальною астмою (32,35 %). Побутовими предикторами розвитку алергічних захворювань в обстежених дітей були проживання в помешканнях, в яких більше ніж 10 років не було ремонту, та утримання в помешканнях домашніх тварин (для підлітків із бронхіальною астмою ВШ = 3,56, ДІ [1,08; 11,68] та ВШ = 6,27, ДІ [1,26; 31,29]; для дітей з алергічним ринітом і дистальним прикусом ВШ = 4,62, ДІ [1,35; 15,78] та ВШ = 6,39, ДІ [1,24; 32,89]. Встановили гіперчутливість підлітків з бронхіальною астмою до алергенів домашнього пилу (35,29 %), кліща побутового пилу Dermatofagoides pteronissinus (29,41 %), епідермісу кота (23,53 %), а дітей з алергічним ринітом і дистальним прикусом – до кліщів побутового пилу Dermatofagoides pteronissinus (50,00 %) і Dermatofagoides farinae (42,86 %), домашнього пилу (42,86 %), епідермальних алергенів кота (42,86 %) та кроля (17,86 %). У сім’ях дітей з алергічними захворюваннями вірогідно частіше використовували косметику, шампуні, мило для купання, що містили формальдегід, парабени, триклозан, лаурилсульфат натрію, а для миття посуду – засоби, що містили поверхнево-активні речовини, ніж у родинах здорових. Висновки. Профілактика бронхіальної астми в підлітків та алергічного риніту та дистального прикусу в дітей включала елімінаційні заходи та призначення алерген-специфічної імунотерапії щодо позитивно значущих алергенів за резуль¬татами алерготестування, поліпшення побутових умов проживання зі своєчасним ремонтом в оселях, застосуванням гіпоалергенних косметичних засобів, шампунів, мила, гелів, використанням для миття посуду засобів без поверхне¬во-активних речовин або ретельне його ополіскування проточною водою. Цель работы – определение бытовых предикторов развития бронхиальной астмы у детей-подростков и аллергического ринита у детей с дистальным прикусом, имеющих персистирующее клиническое течение заболевания. Материалы и методы. Проведено клинико-анамнестическое и аллергологическое обследование 87 детей подросткового возраста (от 13 до 17 лет). І группу наблюдения составили 34 подростка с персистирующим течением бронхиальной астмы, ІІ группу – 28 детей с персистирующим аллергическим ринитом и дистальным прикусом, в связи с чем дополнительно лечились у врача-ортодонта. Контрольную группу наблюдения (ІІІ) составили 25 здоровых детей. Соотношение мальчиков и девочек в группах наблюдения и контрольной группе не имело достоверных различий (р > 0,05). Методом анкетирования изучены ана-мнестические данные, характеризующие бытовые условия проживания, социально-гигиеническое состояние жилья: наличие домашних животных, частота и особенности использования химических моющих и косметических средств у детей. Проведен анализ клинического течения заболеваний. При диспансерном наблюдении в периоде ремиссии детям с персистирующим течением бронхиальной астмы и аллергического ринита при отсутствии противопоказаний к тестированию in vivo с аллер¬генами проведено аллергологическое обследование путем постановки кожных прик-тестов с бытовыми и эпидермальными аллергенами производства ООО «Иммунолог» (г. Винница). При сравнении статистических совокупностей использовали непараметрический статистический метод «2 × 2 Table», the Chi-square (df = 1) и рассчитывали отношение шансов (ОШ) с использованием четырехпольной таблицы и доверительный интервал (ДИ) методом Woolf. Непараметрическим методом gamma correlation (рекомендуется использовать, если есть много совпадающих значений) проведен анализ корреляционной связи между показателями гиперчувствительности к аллергенам. Различия р < 0,05 при сравнении показателей в группах наблюдения и контрольной группе считали статистически достоверными. Результаты. Персистирующее течение хронического аллергического респираторного синдрома средней степени тяжести достоверно чаще регистрировали у детей с аллергическим ринитом и дистальным прикусом (75,00 %), чем у подростков с бронхиальной астмой (32,35 %). Бытовыми предикторами развития аллергических заболеваний у обследованных детей были проживание в помещениях, в которых больше чем 10 лет не было ремонта, и содержание в квартирах домашних животных (для подростков с бронхиальной астмой ОШ = 3,56, ДИ [1,08; 11,68] и OШ = 6.27, ДИ [1,26; 31,29]; для детей с аллергическим ринитом и дистальным прикусом ОШ = 4,62, ДИ [1,35; 15,78] и ОШ =6,39, ДИ [1,24; 32,89]. Диагностирова¬на гиперчувствительность подростков с бронхиальной астмой к аллергенам домашней пыли (35,29 %), клеща бытовой пыли Dermatofagoides pteronissinus (29,41 %), эпидермальным аллергенам кота (42,86 %) и кролика (17,86 %). В семьях детей с аллергическими заболеваниями достоверно чаще использовали косметику, шампуни, мыло для купания, которые содержали формальдегид, парабены, триклозан, лаурилсульфат натрия, а для мытья посуды – средства, содержащие поверхностно-активные вещества, чем в семьях здоровых детей. Выводы. Профилактика бронхиальной астмы у подростков и аллергического ринита и дистального прикуса у детей включала элиминационные мероприятия, назначение аллерген-специфической иммунотерапии с причинно-значимыми аллергенами, улучшение бытовых условий проживания со своевременным проведением ремонта, использование гипоаллергенных косметических средств, шампуней, мыла, гелей и средств для мытья посуды без поверхностно-ак¬тивных веществ или тщательное ополаскивание ее проточной водой.
Характеристика побутових предикторів персистуючого перебігу бронхіальної астми у дітей-підлітків та алергічного риніту у дітей із дистальним прикусом
Характеристика бытовых предикторов персистирующего течения бронхиальной астмы у детей-подростков и аллергического ринита у детей с дистальным прикусом
Keywords: allergic rhinitis; asthma; adolescents; children; malocclusion; алергічний риніт; бронхіальна астма; персистуючий перебі; підлітки; діти; дистальний прикус; аллергический ринит; бронхиальная астма; персистирующее течение; подростки; дети; дистальный прикус